The Influence of Biomotor Abilities on Badminton Athlete Candidate Selection at Medan City Sports Department 2025 - Sitepu, Ricky Ariya; Rizqiansyah, Ridho; Nst, Fuad Diansyah; Butar Butar, Patrick Willyam M; Sinurat, Fajar Rahmansyah (Jurnal Inovasi Olahraga, 2025)
Introduction: Biomotor abilities play a crucial role in badminton athlete selection processes. These fundamental motor capacities determine athletic performance and success potential in competitive badminton.  Purpose of the study: This study aims to analyze the influence of biomotor abilities on the selection process of badminton athlete candidates at the Medan City Sports Department (Dispora) in 2025.  Materials and methods: A quantitative descriptive study was conducted involving badminton athlete candidates participating in the Medan City Sports Department selection program. Biomotor components measured included speed, agility, leg power, coordination, strength, flexibility, and aerobic endurance. Data collection used standardized physical fitness tests and statistical analysis employed multiple regression analysis.  Results: The results showed that biomotor abilities significantly influence athlete selection outcomes, with coordination (β=0.673, p<0.001) and leg power showing the strongest predictive values for badminton performance. The combined biomotor variables explained 65.4% of the variance in selection success (R²=0.654, F=30.700, p<0.001). Conclusions: Biomotor abilities serve as valid and reliable predictors for badminton athlete selection, with coordination and explosive leg power being the most critical factors for success in the selection process.